If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -3i)(5 + 4i) = 0 Multiply (2 + -3i) * (5 + 4i) (2(5 + 4i) + -3i * (5 + 4i)) = 0 ((5 * 2 + 4i * 2) + -3i * (5 + 4i)) = 0 ((10 + 8i) + -3i * (5 + 4i)) = 0 (10 + 8i + (5 * -3i + 4i * -3i)) = 0 (10 + 8i + (-15i + -12i2)) = 0 Combine like terms: 8i + -15i = -7i (10 + -7i + -12i2) = 0 Solving 10 + -7i + -12i2 = 0 Solving for variable 'i'. Factor a trinomial. (2 + -3i)(5 + 4i) = 0Subproblem 1
Set the factor '(2 + -3i)' equal to zero and attempt to solve: Simplifying 2 + -3i = 0 Solving 2 + -3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3i = 0 + -2 -3i = 0 + -2 Combine like terms: 0 + -2 = -2 -3i = -2 Divide each side by '-3'. i = 0.6666666667 Simplifying i = 0.6666666667Subproblem 2
Set the factor '(5 + 4i)' equal to zero and attempt to solve: Simplifying 5 + 4i = 0 Solving 5 + 4i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4i = 0 + -5 4i = 0 + -5 Combine like terms: 0 + -5 = -5 4i = -5 Divide each side by '4'. i = -1.25 Simplifying i = -1.25Solution
i = {0.6666666667, -1.25}
| 2x-9+2x=x-3 | | z^2-3z+2iz+3i+1=0 | | 10=-5(p+5) | | 10x-1=6x+3 | | (-4+7)-(6+11i)=0 | | 2m-5=6m+11 | | 4x=-208 | | .22=logx | | 4x-3=52 | | (3+2i)I=0 | | .22=logs | | (-4+5i)+(3-2i)=0 | | x^2-18y=13 | | 4cos^2x+4sinx-5=0 | | 4y-6+6y+6=90 | | 1.5t=180 | | 15n=-60 | | 42+2y=24 | | 3x-50=x+80 | | x-20=-23 | | 25x+7=17.00 | | 0.5x^2=-2x+3 | | 4x-4=6x-12 | | x-20=-20 | | -3x=-40 | | Y=-11x+9 | | 15y=-3x+9 | | 5(c+2)=30 | | 5(x+12)=140 | | 18=-6k+6+10k | | 1.99(342)=480+x | | (2X+72)-9(X+22)= |